(untitled) (Fiep Bulletin - online, 2015)
In this paper an evaluation of a warming up model of passive/static flexibility is presented, with the main goal of a good preparatory work for sport practices and a high performance in exercise execution. Eight students from twelve to fourteen years-old, of both genders, have participated in the experiment, carried out at the Artistic Gymnastics Gym at UFRGS. The students were evaluated through two movements. In the first one, they were sitting down with the knees extended and hip flexion (piked movement). The coxofemoral joint with the knee joint were analyzed as anatomic points of reference and quantified in grades. In the second one, the students’ flexibility was measured with legs abduction, in dorsal decubit position and hip flexion. The frontal split opening was measured with the support of a goniometer on the pubic region. The warming up model, with variation in the passive/static execution and great concentration in the legs, was made for fifteen minutes in the beginning of all activities, in a period of one month with twelve meetings. One Pre-Test and one Post-Test was performed in both elements, in separated female and male groups. In all the results an increase in the students’ flexibility could be observed. The improvements verified were of 12o in the piked exercise for males, 11o in the piked exercise for females, 23o in the frontal split for males, 49,5o in the frontal split for females, 12o in the general piked exercise and 36o in the general frontal split. The results let us conclude that the application of the passive/static method provides a significant increase of the inferior members amplitude.